This is a file in the archives of the Stanford Encyclopedia of Philosophy. |
FUNC: Let A be a self-adjoint operator associated with observable A, let f: RIn order to derive Sum Rule and Product Rule from FUNC, we use the following mathematical fact: Let A and B be commuting operators, then there is a maximal operator C and there are functions f, g such that A = f(C) and B = g(C).R be an arbitrary function, such that f(A) is self-adjoint operator, and let | f > be an arbitrary state; then f(A) is associated uniquely with an observable f(A) such that:
v(f(A))= f(v(A))
Sum Rule: If A and B are commuting self-adjoint operators corresponding to observables A and B, respectively, then A + B is the unique observable corresponding to the self-adjoint operator A + B and
v(A + B)= v(A)
+ v(B)
Product Rule: If A and B are commuting self-adjoint operators corresponding to observables A and B, respectively, then if A
B is the unique observable corresponding to the self-adjoint operator A
B and
v(AB)= v(A)
![]()
v(B)
So, for two commuting operators A, B:
Since A = f(C) and B = g(C), there is a function h = f+g, such that A + B = h(C).Therefore:
Similarly:
v(A + B) = h(v(C) )
(by FUNC) = f(v(C) ) + g(v(C)
)
= v(f(C)) + v(g(C))
(by FUNC) = v(A) + v(B)
(Sum Rule)
Since A = f(C) and B = g(C), there is a function k = fTherefore:g, such that A
B = k(C).
v(A B)
= k(v(C) )
(by FUNC) = f(v(C) )
g(v(C)
)
= v(f(C)) ![]()
v(g(C))
(by FUNC) = v(A) ![]()
v(B)
(Product Rule)
Return to The Kochen-Specker Theorem
Carsten Held carsten.held@uni-erfurt.de |